A THE EFFECT OF DOSE AND TIME OF ADMINISTRATION OF TRICHODERMA SP ON FUSARIUM OXYSPORUM ON SHALLOT (Allium ascalonicum L): Trichoderma sp, fusariumi oxysporum. - Yasintasari, Afik Yasintasari; Hadi, Pramono; Mukti Prabowo, Shalahudin (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2021)
ABSTRACT This studypaimsptopdeterminepthe appropriate dosepand time ofxadministration ofxTrichoderma sp to control Fusarium oxysporum disease in shallot plants. Thepresearch waspconductedpfrompSeptemberp2020ptoxDecemberx2020 in Karangasem Hamlet, Guli Village, Nogosari District, Boyolali Regency. Thispstudypusedpapfactorialpcompletely randomizedpdesign (RAL) methodpwhich consisted ofp2pfactors. Thepfirst treatmentpfactor was thepdose ofpTrichoderma sp (D) which consisted of 3 g, 5g, 7g and the time of administration (T) which was one week before planting, during planting and a week after planting. Parameterspobservedpwerepnumberpof leaves, number ofptubers, weightpof fresh stover, weight of dry stover and intensity of disease attack. The results showed that the treatment with the best Trichoderma sp (D) dose was obtained in the D3 treatment with a dose of 7 grams / liter of solution had a very significant effect on the number of leaves, fresh stover, dry stover, intensity of disease attack and not significantly different on the number of tubers. The best time treatment for giving Trichoderma sp (T) was obtained in T1 treatment, namely the time of administration one week before planting had a significant effect on the number of leaves, fresh stover, and was not significantly different on the number of tubers, dry stover, intensity of disease attack. Meanwhile, the best combination of dosage and time of administration of Trichoderma sp was obtained in the (D3T1) treatment, namely the administration of a dose of 7 grams / liter of solution and the time of administration one week before planting had a significant effect on dry stover and had no significant effect on other parameters. Keywords : Trichoderma sp, fusarium oxysporum, shallot.